Faktor yang Menggalakkan Penglibatan Siswi di dalam Sukan Wanita: Satu Tinjauan Kualitatif - Ani Mazlina Dewi Mohamed; Rozita Abdul Latif; Lily Anak Kada; Mohd. Sofian Omar Fauzee; Marjohan Jamalis (UiTM Publisher, 2008)
The objective of this research is to identify factors that influence the involvement of female university students in sports. Ten university students who were involved in the National Women's Sports 2007 agreed to be interviewed. These respondents agreed to be taperecorded during the data collection for this research. All recordings were transcribed and analyzed thematically. The three main themes that emerged from the analysis were: involvement in sports, intrapersonal and interpersonal aspects. The findings show that excitement was the main factor for the female students' involvement in sports. The recommendations and other findings are also discussed in this research.